1993
DOI: 10.1557/jmr.1993.1675
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Li-salt additions on the densification of tin oxide

Abstract: Sintering of pure SnO 2 to high densities is difficult due to its high vapor pressure, and hence, additives are typically used to enhance densification. In this study, the effects of two lithium compounds, LiF and LiNO 3 , on the densification behavior of SnO 2 were evaluated. While LiF resulted in only a modest improvement in densification, LiNO 3 additions resulted in densities of 5=95% theoretical at 1500 °C in air. Thermal, x-ray, and SEM/TEM microstructural analyses indicated no liquid phase formation. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…They attributed the high densification to the increased concentration of oxygen vacancies in the grain boundary region, with the proposed reaction for the formation of oxygen vacancies when SnO 2 is doped with Co. These results are in agreement with the work of Yuan et al [23] who demonstrated that the Li + ion also promotes SnO 2 densification by increasing the flux of species that diffuse inside the material. Pianaro et al [24] observed that when the basic SnO 2 varistor is doped with Cr 2 O 3 the grain size decreased, indicating that Cr 2 O 3 inhibits grain growth during sintering.…”
Section: Microstructural Characterizationsupporting
confidence: 86%
“…They attributed the high densification to the increased concentration of oxygen vacancies in the grain boundary region, with the proposed reaction for the formation of oxygen vacancies when SnO 2 is doped with Co. These results are in agreement with the work of Yuan et al [23] who demonstrated that the Li + ion also promotes SnO 2 densification by increasing the flux of species that diffuse inside the material. Pianaro et al [24] observed that when the basic SnO 2 varistor is doped with Cr 2 O 3 the grain size decreased, indicating that Cr 2 O 3 inhibits grain growth during sintering.…”
Section: Microstructural Characterizationsupporting
confidence: 86%
“…This is potentially an important point as several papers have reported improved performance for ceramic materials sintered in the presence of a liquid phase. [49][50][51] Figure 2 shows XRD data and Raman spectra for films sprayed from nickel nitrate solutions with and without 5 wt % LiNO 3 added. The lithium nitrate loading level was fixed based on separate experiments that demonstrated no significant improvement in film performance for loadings higher than 5% ͑data not shown͒.…”
Section: Resultsmentioning
confidence: 99%
“…LabVIEW has been already used in X-ray imaging for large scale CT tomographic reconstruction software development [5], X-ray flat-panel detector driver design [6] and CT imaging system software building [7][8][9] by different teams. In addition, the LabVIEW's Vision Development Module (VDM) provides an excellent tool to perform digital image processing [10,11], the utilization of the VDM reduces the complexity and shortens the development cycle. The newly released LabVIEW Biomedical Workbench Toolkit (BWT) includes also a 3D image reconstruction module, which could reconstruct a 3D model from a set of 2D image slices.…”
Section: Introductionmentioning
confidence: 99%